PENGARUH PROFITABILITAS, SIZE DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN BISNIS-27 YANG TERDAPAT DI BURSA EFEK INDONESIA - Meizari, Ary; Viani, Tri Okta (Jurnal Manajemen Magister Darmajaya, 2017)
Firm  Value  is  influenced  by  the  financial  performance  of  a  company.  Financial performance is reflected by stock prices and shown in a good performance as well as how the company uses its assets to get maximum profit. The purpose of this study wasto determine the impact of profitability, size, and debt policy to firm value on companies in business27 index at the Indonesia Stock Exchange. The analysis of the data used in this research  was  multiple  linear  regression.  The  result  showed  that  the  profitability  had significant effect on value of firm. The size had significant effect on firm value. The debt policy had significant effect on firm value. The F test results showed that Profitability, Size and Debt Policy had significant effect on firm value at the companies in business27 index atthe Indonesia Stock Exchange. Kata Kunci  : Profitabilitas, Size, Kebijakan Hutang, Nilai Perusahaan.